Settings, populations, and time: a conceptual framework for public health interventions - Aagaard-Hansen, Jens; Bloch, Paul (Frontiers in Public Health, 2023)
This paper presents a conceptual framework displaying how combinations of settings and populations seen in a long-term perspective may guide public health and health promotion planning and research. The notion of settings constitutes a key element of health promotion as stipulated by the Ottawa Charter from 1986. The setting approach highlights the individual, social and structural dimensions of health promotion. Likewise, the notion of populations and how they are selected forms a center pillar of public health. By joining the two perspectives, four combinations of intervention strategies appear by addressing: (1) a single population segment within a single setting, (2) multiple population segments within a single setting, (3) a single population segment within multiple settings or (4) multiple population segments within multiple settings. Furthermore, the addition of a time dimension inspired by the life-course perspective illustrates how trajectories of individuals and projects change settings and population segments as time goes by. The conceptual framework displays how systematic awareness of long-term, multi-setting, multi-population trajectories allow health promotion planners and researchers to systematically develop, plan and analyze their projects.